Entrepreneurial, Innovative and Sustainable Ecosystems Best Practices and Implications for Quality of Life (Applying Quality of Life Research, Best Practices,, 2018)
This book presents a multidimensional approach by providing a state of the art on EIS ecosystems, as well as structural and changing dynamics and its impact on citizens' quality of life. It provides a set of international benchmarking case studies on good practices and initiatives aimed at creating and fostering EIS ecosystems. It shows how these international benchmarks can be replicated to foster the creation of entrepreneurial and innovative units and promote sustainable practices, under an open innovation paradigm, which conjoins the participation of both public and private stakeholders, using co-creation, transparency and participatory budget practices the jointly improve accountability and public management.This book is a true reference guide for scholars, policy makers and practitioners interested on entrepreneurship, public procurement, innovation and sustainability engaged in building EIS ecosystems, which can enhance citizens' quality of life.